The Use of Bubble CPAP and Humidified High Flow Nasal Cannula Oxygen Therapy in Children with Severe Pneumonia and Hypoxemia: A Systematic Review of the Evidence - Chisti, Mohammod Jobayer; Duke, Trevor; Ahmed, Tahmeed; Shahunja, KM; Shahid, Abu SMSB; Faruque, Abu SG; Ashraf, Hasan; Bardhan, Pradip Kumar; Graham, Stephen M; Salam, Mohammed Abdus (Bangladesh Critical Care Journal, 2015)
Background: Among children with severe pneumonia hypoxemia is the commonest complication leading to death. Some children will have both type I (hypoxemic) and type II (hypercarbic) respiratory failure. Together this accounts for high case-fatality rates in most populations with severe pneumonia. Standard oxygen supplementation by nasal prongs (low flow) can be lifesaving, but is not always sufficient to manage respiratory failure. In recent years continuous positive airway pressure (CPAP) has been used to relieve hypoxemia and reduce the work of breathing. There are several ways to give positive airway pressure; one is bubble CPAP (BCPAP), another is high flow nasal cannula (HFNC) oxygen therapy. Objective: To review the evidence for using BCPAP, and HFNC therapy in children with severe pneumonia and hypoxemia, particularly the experience of these therapies in developing countries. Methods: Two of our study investigators independently conducted searches of the existing literature in PUBMED in October 2014 to identify reports focusing on the use of BCPAP or HFNC therapy in children with severe pneumonia and hypoxemia, as defined by the World Health Organization. Results: 13 relevant studies were identified. Ten evaluated the efficacy of BCPAP among 3164 children, and three described the same for HFNC in 255 children. In all studies the entry criteria was severe respiratory distress. The study methodologies, the outcomes recorded and results were heterogeneous. The age range of the children in the studies was from the immediate newborn period on day 1 of life up to the age of 12 years. However, we evaluated the outcome of our review in two aged categories and found: children 0-28 days for 8 studies and > 28 days for 2 studies. In 3 studies of children aged 0-28 days and 2 studies of older children had clinical features consistent with severe pneumonia and those who among them were treated with immediate BCPAP therapy had better outcome (p<0.01 or CI < 1) compared to those who were treated with delayed BCPAP, or historical control one each, or standard flow flow (LF) oxygen therapy (in two studies). Primary outcomes were comparable between BCPAP and ventilator driven CPAP in three studies and between BCPAP and low flow oxygen or variable flow nasal CPAP in two studies (95% CI contain 1) of children aged 0-28 days. Children treated with HFNC compared to those who did not receive HFNC in three relevant studies, all of them in older children had better outcome (p<0.05). Conclusion: Studies of BCPAP and HFNC are heterogeneous with different populations, comparators, outcome measures and results. However limited studies suggest that BCPAP may be effective in managing respiratory distress and hypoxemia in developing countries, although evidence is not overwhelming. Studies of the use of HFNC therapy are more limited and do not allow firm conclusions to be made. Most studies of BCPAP and HFNC have been done in neonates with respiratory distress, and studies outside this age group, where the predominant pathologies are bacterial pneumonia, sepsis and viral bronchiolitis are needed. Bangladesh Crit Care J September 2014; 2 (2): 71-78